THE IMPACT OF EMPLOYEE MOTIVATION ON SERVICE QUALITY AND COMMUNITY SATISFACTION WITHIN PUBLIC SERVICE QUALITY IN THE DISTRICT OF SOUTH TANGERANG - Wiwin Siswantini; Tamjuddin .; Devi Ayuni; Andy Mulyana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
South Tangerang is a new autonomous region in Banten Province that is established by Act No. 51 of 2008. The new autonomous region in Banten as expansion of Tangerang Regency has 7 districts. Based on Population Census in 2014 has 1.405.170 inhabitants. Population of male is 708.767 inhabitants and population of female is 696.403 inhabitants. Information found directly and through various media frequently reveals weaknesses of government services which reflect community dissatisfaction with the service personnel. The level of community satisfaction with the services of the community sector is still quite low, it is evidenced from several empirical studies on the quality of service in local government bureaucracy. Based on the initial observation, work motivation of goverment officials is played a role in realizing the quality of public services in the district of South Tangerang. Hence the author is interested in further researching and analyzing the impact of work motivation and service quality of apparatus to satisfaction community in the district level of South Tangerang. This study use nonprobability sampling as the sampling method. For the purposes of quantitative analysis, the determination of the score for each item questionnaire is used a Likert Scale. The processing data in this study is using SEM with support of software LISREL 8.7. The result of study shows that the motivation of civil servants apparatus district in South Tangerang is affecting the quality of service however is not affecting community satisfaction. This is due to the unfavorable work environment and leadership role in the completion of the assignment. Meanwhile the quality of service of civil servants apparatus affects people's satisfaction in districts in South Tangerang.